Designing an Arabic language module for non-Arabic speakers working in the commercial sector in the middle east - Ahmed Mohamed, Ismaiel Hassanein (s.n, 2013)
The fact that most of books written in the field of teaching Arabic to non-native speakers do not fulfill the needs of business group who are interested in learning Arabic for business purposes in their career life triggered this research, given the researcher's professional observation